Can Wage Transparency Alleviate Gender Sorting in the Labor Market? - Omar Bamieh; Lennart Ziegler (Institute of Labor Economics (IZA), 2022)
Wage decompositions suggest that a large share of the gender wage gap can be explained by differences in occupation and employer choices. If female workers are not well informed about these pay differences, increasing wage transparency might alleviate the gender gap. We test this hypothesis by examining the impact of the 2011 Pay Transparency Law in Austria, which requires companies to state a wage figure in job advertisements. For the analysis, we combine vacancy postings from the largest Austrian job board with social security spells that record the gender of new hires. To compare the pay level of vacancies before and after the reform, we predict wage postings using detailed occupation-employer cells, which explain about 75 percent of the variation in posted wages. While we estimate a substantial gender wage gap of 15 log points, pay transparency did not affect gender sorting into better-paid occupation and firms. To study job transitions, we focus on a subsample of workers whose previous employment is also observed. Our estimates show that switching occupations is common, and it often entails significant wage changes. Yet, in line with our main estimates, we do not find that women become more likely to switch to better-paid jobs. We interpret the absence of effects as evidence that limited transparency does not explain the persistence of gender sorting in the labor market.
Keywords: J16; J31; J62; J63; J68; 330; gender differences; wage postings; pay transparency; job vacancies; labor market sorting